Computerised tomography and acute traumatic head injury: time for change?. Issue 2 (March 1996) - Cranshaw, J; Hughes, G; Clancy, M
Abstract : The aim was to reconsider the "Guidelines for initial management of head injury in adults"–particularly with respect to the indications for computerised tomographic (CT) scanning–suggested by "a group of neurosurgeons" over a decade ago and still followed in some accident and emergency (A&E) departments. These recommendations are placed in the context of more recent research and the increased number of A&E departments with on-site rapid access to a CT scanner but without a resident neurosurgical facility. A case can be made for an updated policy with more liberal indications for CT scanning of acutely head injured adults in peripheral A&E departments. However, calculating the cost-efficiency of more frequent use of what is now a common but relatively expensive resource would remain a challenge.